Intraflagellar transport trains can switch rails and move along multiple microtubules in intact primary cilia - Shufeng Sun; Biqing Liang; Adam Koplas; Irina Tikhonenko; Maxence Nachury; Alexey Khodjakov; Haixin Sui (Proceedings of the National Academy of Sciences, 2025)
Structural homeostasis and proper distributions of signaling molecules in cilia require a constant flow of cargoes carried by intraflagellar transport (IFT) trains in both anterograde and retrograde directions within the thin, long ciliary shafts. In the motile cilium framework, the nine microtubule doublets of the same length serve as the transportation rails, and a preferential association to the two subtubules of the microtubule doublets prevents collisions among the IFT trains that move in opposite directions. However, this mechanism is incompatible with the primary cilia structure, where most of the nine microtubule doublets terminate in the ciliary shafts—only several of them reach the ciliary tip and only in a singlet form. Here, we demonstrate that anterograde and retrograde trains in primary cilia interact with both subtubules of the microtubule doublets without apparent preference. They can switch microtubules, and they may simultaneously interact with multiple microtubules to facilitate their movement. This architecture makes the collisions inevitable, and live-cell recordings reveal that anterograde and retrograde trains tend to pause when they come into direct contact. We also find that the velocity of the train’s movement often changes after the pause. Thus, the motion behaviors of IFT trains in primary cilia are distinctive from those of motile cilia, and our data offer an essential foundation for understanding proper signaling molecule distributions in primary cilia.